Geometry and Conservation Laws for a Class of Second-Order Parabolic Equations II: Conservation Laws - McMillan, Benjamin B. (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
I consider the existence and structure of conservation laws for the general class of evolutionary scalar second-order differential equations with parabolic symbol. First, I calculate the linearized characteristic cohomology for such equations. This provides an auxiliary differential equation satisfied by the conservation laws of a given parabolic equation. This is used to show that conservation laws for any evolutionary parabolic equation depend on at most second derivatives of solutions. As a corollary, it is shown that the only evolutionary parabolic equations with at least one non-trivial conservation law are of Monge-Ampère type.